1996
DOI: 10.1007/s002030050318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chlorobenzoates on the utilisation of chlorobiphenyls and chlorobenzoate mixtures by chlorobiphenyl/chlorobenzoate-mineralising hybrid bacterial strains

Abstract: Chlorobenzoates (CBA) arise as intermediates during the degradation of polychlorinated biphenyls (PCBs) and some chlorinated herbicides. Since PCBs were produced as complex mixtures, a range of mono-, di-, and possibly trichloro-substituted benzoates would be formed. Chlorobenzoate degradation has been proposed to be one of the rate-limiting steps in the overall PCB-degradation process. Three hybrid bacteria constructed to have the ability to completely mineralise 2-, 3-, or 4-monochlorobiphenyl respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The latter include the use of halobenzoates as herbicides and formation during microbial degradation of these compounds (24). Chlorobenzoates (CBas) are also intermediates produced during aerobic biodegradation of polychlorinated biphenyls (PCBs), and in this process CBa degradation is important as accumulation of metabolites produced from CBas (i.e., chlorocatechols and protoanemonin) may result in feedback inhibition and impede PCB biotransformation (1,7,8,25,48,49). Thus, optimization of CBa degradation by using inoculants or genetically engineered strains can improve the effectiveness of PCB bioremediation (5,16,26,29,31,(39)(40)(41).…”
mentioning
confidence: 99%
“…The latter include the use of halobenzoates as herbicides and formation during microbial degradation of these compounds (24). Chlorobenzoates (CBas) are also intermediates produced during aerobic biodegradation of polychlorinated biphenyls (PCBs), and in this process CBa degradation is important as accumulation of metabolites produced from CBas (i.e., chlorocatechols and protoanemonin) may result in feedback inhibition and impede PCB biotransformation (1,7,8,25,48,49). Thus, optimization of CBa degradation by using inoculants or genetically engineered strains can improve the effectiveness of PCB bioremediation (5,16,26,29,31,(39)(40)(41).…”
mentioning
confidence: 99%
“…24) This phenomenon has been described during the biodegradation of polychlorinated biphenyls (PCBs), where microorganisms usually metabolize only one aromatic ring and accumulate the others as the corresponding chlorobenzoates. 25,26) …”
Section: Biodegradation Of Aniline and N-methylaniline By Planktonic mentioning
confidence: 99%
“…Chlorinated benzoic acids are common contaminants and arise as byproducts of PCB or chlorinated herbicide degradation [7,8]. For example, Fava et al [9] observed increases in 2CBA and 2,5‐dichlorobenzoic acid (25diCBA) concentrations during PCB degradation in a bioreactor.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fava et al [9] observed increases in 2CBA and 2,5‐dichlorobenzoic acid (25diCBA) concentrations during PCB degradation in a bioreactor. Furthermore, PCB‐contaminated sites will contain mixtures of chlorinated benzoic acids as the PCB mixture present in commercial PCB formulations (e.g., Aroclor™ 1260) degrades [8]. The occurrence of contaminant mixtures may pose a problem in site remediation because one toxic component of the mixture may limit degradation of other contaminants.…”
Section: Introductionmentioning
confidence: 99%